The Use of Information and Communication Technology (ICT) In Learning Writing Narrative - AGUS ROFI'I (Journal of English Language Learning, 2021)
This study aims to describes narrative writing skills are one aspect of language skills that are very important. Learning to write until now is still a lesson that is less attractive to students. One of the things that causes it learners are less interested in the teaching of writing is the selection of instructional media, need for learning as something that is fun, comforting, and easy is something that is urgent due to the development of modernization in various fields. One of them is information and communication technology (ICT), through the use of media, it is hoped that it can help facilitate students in expressing ideas to be developed into a narrative essay. The use of media has the possibility to be used as an alternative method in an effort to develop narrative writing learning. It is expected that most students are happy and interested in learning using media. In addition, the media can help the difficulties of students in determining topics in their narrative.